Effect of extreme temperature on egg development, larval and adult survival of Chordodes nobilii Camerano, 1901 (Gordiida, Nematomorpha) - Achiorno, Cecilia Luján (2008)
On the basis of experimental studies we analyzed the effect of extreme temperatures on the aquatic free-living phases of the life cycle of Chordodes nobilii (Gordiida, Nematomorpha). Bioassays were performed with eggs, larvae, and adults. Eggs and larvae were exposed to 3°C below zero and 40.5°C; adults were exposed to 3°C below zero and to 38.5°C and 40.5°C. The results showed that egg development was inhibited in both tests. Exposed larvae showed a decrease in their infective capacity, which resulted almost null at 40.5°C. Adults exposed to 38.5°C showed mortality ≤10%, at 40.5°C the mortality was 100% and the adult's mortality at 3°C below zero was 89%. Results indicate that free living stages of Chordodes nobilii are susceptible to extreme temperatures.